Preterm birth and cerebral palsy - Monica Topp; Jens Langhoff‐Roos; Peter Uldall (Acta Obstetricia et Gynecologica Scandinavica, 1997)
Background. Preterm infants are at 8 times higher risk than term infants for pre‐ and perinatal brain damage, resulting in cerebral palsy. In this paper we have analysed the influence of prenatal and birth‐related risk factors on cerebral palsy in preterm infants. Methods. In a register‐based study, 175 preterm singleton infants with cerebral palsy, born in 1982‐86, were compared with 687 controls matched by gestational age and year of birth. Results. Statistically significant higher rates in cases were found in parity ≥3 (22% vs. 16%, p<0.05), Cesarean section (67% vs. 56%, p<0.01), and low Apgar scores at 1 minute (45% vs. 36%, p<0.05). By multivariate analyses, two variables remained statistically significant: parity ≥3 (adjusted OR=1.53 (95% CI 1.00‐2.34), p<0.05) and Cesarean section (adjusted OR=1.57 (95% CI 1.07‐2.32), p<0.05). Conclusions. Pregnancy complications preceding preterm birth did not imply a higher risk of cerebral palsy. Delivery by Cesarean section was a prognostic factor for developing cerebral palsy, and the predictive value of Apgar scores was highly limited.